Immunophenotypic features of dedifferentiated skull base chordoma: An insight into the intratumoural heterogeneity - Batista, Kelvin Manuel Pińa; Reyes, Kenia Yoelvi Alvarez; Lopez, Fátima Pérez; Pelaz, Andrés Coca; Vega, Ivan Fernandez; Pendás, José Luis Llorente; Ayala, Antonio Saiz; Astudillo, Aurora; Rojas, Jorge Andrés Nuńez; Fernandez, Patricia Barrio (Contemporary Oncology/Współczesna Onkologia, 2017)
Chordomas are rare and low-grade malignant solid tumours, despite their histologically benign appearance, that arise in the bone from embryonic notochordal vestiges of the axial skeleton, a mesoderm-derived structure that is involved in the process of neurulation and embryonic development. Chordomas occurring in the skull base tend to arise in the basiocciput along the clivus. Three major morphological variants have been described (classical, chondroid, and atypical/dedifferentiated). The pathogenesis and molecular mechanisms involved in chordoma development remain uncertain. From a pathological standpoint, the microenvironment of a chordoma is heterogeneous, showing a dual epithelial-mesenchymal differentiation. These tumours are characterised by slow modality of biologic growth, local recurrence, low incidence of metastasis rates, and cancer stem cell (CSC) phenotype. The main molecular findings are connected with brachyury immunoexpression and activation of the downstream Akt and mTOR signalling pathways. The differentiation between typical and atypical chordomas is relevant because the tumoural microenvironment and prognosis are partially different. This review provides an insight into the recent and relevant concepts and histochemical markers expressed in chordomas, with special emphasis on dedifferentiated chordomas and their prognostic implications.